The unexpected and unanticipated announcement of the “world’s first” gene edited babies: breaching, repairing and strengthening community boundaries - Rebecca Dimond; Jamie Lewis; Alice Sumner (New Genetics and Society, 2023)
The 2018 announcement that the world’s first babies had been born following gene editing was unexpected and unanticipated. In this article, we focus on the reaction to the announcement and explore how this revealed implicit and explicit assumptions about the role and responsibilities of scientists and scientific standards. Through analysis of media coverage and public commentary about the birth of the “world’s first,” we identify how the event was constructed as a breach of scientific norms. We begin by identifying the use of an “if true” narrative, which contributed to the meanings of the technology and the births following the initial announcement. We consider two dimensions to the concept of “breach,” as an individual act of transgression and as a rupture of community norms. Finally, we consider the work of the broader scientific community in repairing the damage and their attempts to strengthen its boundaries to prevent future transgressions.